2013
DOI: 10.1016/j.injury.2011.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Do compensation processes impair mental health? A meta-analysis

Abstract: Being involved in a compensation process is associated with higher mental health complaints but three-quarters of the difference appeared to be already present at baseline. The findings of this study should be interpreted with caution because of the limited quality of evidence. The difference at baseline may be explained by a selection bias or more anger and blame about the accident in the compensation group. The difference between baseline and follow-up may be explained by secondary gain and secondary victimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
72
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 51 publications
2
72
0
Order By: Relevance
“…Compensation participants, particularly those with a poorer baseline health profile may be more vulnerable to the impact of the system complexities [9][10][11] which have been found to have a negative impact on health and recovery [6]. However, a poor baseline health profile does not wholly account for the poorer psychological and physical health seen post injury [6,11] perhaps suggesting that the causal relationship occurs cyclically, in the manner of a vicious cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compensation participants, particularly those with a poorer baseline health profile may be more vulnerable to the impact of the system complexities [9][10][11] which have been found to have a negative impact on health and recovery [6]. However, a poor baseline health profile does not wholly account for the poorer psychological and physical health seen post injury [6,11] perhaps suggesting that the causal relationship occurs cyclically, in the manner of a vicious cycle.…”
Section: Introductionmentioning
confidence: 99%
“…However, a poor baseline health profile does not wholly account for the poorer psychological and physical health seen post injury [6,11] perhaps suggesting that the causal relationship occurs cyclically, in the manner of a vicious cycle. Prolonged exposure to the scheme increases the likelihood of participants coming into contact with system complexities known to be stressful including; numerous assessments [12] and the overall adversarial nature of dealing with compensation players [13].…”
Section: Introductionmentioning
confidence: 99%
“…This notion of secondary victimisation where claimants experience renewed victimisation because of the stressful compensation process has also been described by others [17,26]. A recent review by Elbers et al [27] suggests that there are significant stressors in the compensation process, among them; numerous assessments, situations where claimants are confronted with the traumatic history of the injury event, delayed funds and financial risks. It has been suggested that claimants with lower general health, particularly mental health at baseline may be more vulnerable to the effects of these stressors [14,26].…”
Section: Discussionmentioning
confidence: 74%
“…It has been suggested that claimants with lower general health, particularly mental health at baseline may be more vulnerable to the effects of these stressors [14,26]. These stressful processes have been associated with increased claim duration [27], increased lawyer involvement [17], and increased health care utilisation [28]. In our study it is possible that this contributes to the ongoing worse health for the group and leads some to seek the assistance of lawyers.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation